PENGARUH MENONTON TAYANGAN TELEVISI TERHADAP PERILAKU AGRESIF PADA ANAK PRASEKOLAH - Atmoko, Andreas Dwi; Munir, Zainal; Ramadhan, Gilang (Jurnal Keperawatan Profesional, 2019)
Television is one of the mass media influence on children's behavior, especially in the process of absorption (internalization) of certain social values. This research aims to analyze The influence of Watching Television Towards Aggressive Behavior to  Preschool Children in TK Aisyah Bondowoso. Design of research using the analytic of correlation with Cross Sectional approach. The population is Preschool Children in TK Aisyah Bondowoso and sample as many as 30 respondents in methods data retrieval of Total Sampling. This research was conducted in October 2015. Data collection was conducted by questionnaire sheet, then the data is tabulated and analysed using the statistical analysis Test correlation Spearman Rho ' with significant degrees of 0,05. So the obtained p value 0.008 meaning H I received there is the influence of Watching Television towards aggressive behavior in Preschool Children in TK Aisyah Bondowoso value correlation r = 0439.The important of knowledge The influence of Watching Television Towards Aggressive Behavior in Preschool Children in TK Aisyah Bondowoso. So for need role of parents to prevent aggressive behavior. Keywords: Watch Television, Aggressive Behavior, Pre School Children